Social and medical aspects of epidemics in pre-revolutionary Maikop - Artur Karpushovich Arutyunov; Irina Nikolaevna Djakova (Вестник Майкопского государственного технологического университета)
The relevance of the research. The emergence of pandemics in the modern society creates the need to study the historical experience of the conditions for the emergence, development and elimination of epidemics.The purpose of the research is to consider the social and medical aspects of epidemics of various origin in the pre-revolutionary Maikop. The research objectives are to analyze the health status of the population of Maikop in the period from 1870 to 1917; to study the dynamics of fertility, mortality and number of population; to imagine the life conditions and activities of people; to assess the social, economic and epidemiological situation in the given period; to consider the level of the development of urban medicine and ways to deal with epidemics. The historical-typological, comparative, and statistical research methods have been used.The research results. Between 1871 and to 1917 in the city of Maikop the population almost quadrupled due to high birth rates (the average birth rate was 50.6%) and numerous migrants. The city survived two large epidemics: in 1872 - that of smallpox, cholera and malaria, in 1892 – cholera and in the same years there was an excess of mortality over births. The sanitary condition of the city of Maikop was poor, the first water pipe was built only in 1911, most households were represented by wooden and adobe houses with courtyards. The inhabitants of the city raised cattle, and were engaged in gardening and arable farming. A minority of the townspeople were factory workers, some traded.Due to the low standard of living, diseases such as malaria, diphtheria, scarlet fever, measles, typhoid recurred annually, and due to the lack of doctors, hospitals, and medicines, they claimed the lives of people. The average mortality rate (excluding years with epidemics) was 35.4%.The conclusions. More than 45 socially and epidemiologically difficult years have passed since the foundation of the city of Maikop until the revolution. City medicine developed slowly, during all this time one hospital, two outpatient clinics and an infectious disease barracks were built. There was one health worker per 1384 inhabitants.